Boeremia parva sp. nov., a novel species of the family Didymellaceae isolated from soil - Das, Kallol; Ten, Leonid N.; Ban, Jae-Ho; Lee, Seung-Yeol; Jung, Hee-Young (Phytotaxa, 2021)
Fungal strains, designated KNU-NL4 and KNU-OL2, belonging to the family Didymellaceae were isolated from a soil sample collected in Miryang, Korea. Phylogenetic analyses based on a concatenated dataset of DNA sequences of ITS regions and partial sequences of ACT, CAL, TEF1-α, and β-TUB genes showed that the isolates reside in a clade together with Boeremia species but occupy the distinct phylogenetic position. Morphologically, the novel strains produce bigger conidiomata (average size 169.8 μm) than the closely related B. rhapontica (126.59 μm) and smaller than the other close neighbor B. coffeae (187.5 μm). Both novel strains also differed from them by smaller colony size and colony color on OA and MEA. The detailed descriptions, illustrations, and discussions regarding the morphological and phylogenetic analyses of the closely related species are provided to support the novelty of the isolated species. The results of phylogenetic analysis and morphological observations indicate that strains KNU-NL4 and KNU-OL2 represent a novel species in the genus Boeremia, for which the name Boeremia parva sp. nov. is proposed.